2018
DOI: 10.1002/aic.16457
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of droplet coalescence propelled by dielectrophoresis

Abstract: We propose dielectrophoretic force driven coalescence of droplets having equal or nonequal sizes with an electrode base actuation system over a solid surface. Coupled electrohydrodynamic conservation equations are solved to simulate the phenomenon based on finite volume scheme. Volume of fluid technique is used to capture the interface. Electric potential and dissimilarity index are varied to comprehend the coalescence dynamics. The interplay between the capillary and electrostatic influences during the coales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Further, as shown in Figure b, there is a clear linear correlation between the free energy and the surface area. Such a correlation indicates that the free energy of the coalescence process is dominated by the surface tension, which is consistent with relevant hydrodynamic studies …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Further, as shown in Figure b, there is a clear linear correlation between the free energy and the surface area. Such a correlation indicates that the free energy of the coalescence process is dominated by the surface tension, which is consistent with relevant hydrodynamic studies …”
Section: Resultssupporting
confidence: 89%
“…For example, Deka et al used the Navier–Stocks (NS) equation for incompressible Newtonian fluids to mimic the coalescence of two droplets, where the dynamic morphology and velocity profiles have been predicted and analyzed to understand the coalescence process. Datta et al used the same theory to examine how a solid dielectric layer affects the coalescence process and found that the initial stage of coalescence is dominated by the surface tension and the electric field becomes effective in a later stage. Rahman et al used the NS equation and experiments to study the bridge growth of the coalescence process and proposed a derivative equation to predict the rate of this process.…”
Section: Introductionmentioning
confidence: 99%
“…Nahar et al [33] investigated another droplet splitting mechanism using the phase separation performance technique. Several research works demonstrated other movement strategies like uphill climbing or coalescence of droplets by electrowetting-on-dielectric actuation [34,35].…”
Section: Related Workmentioning
confidence: 99%
“…The interaction of electric field and fluid, referred to as electrohydrodynamics, has been a research hotspot owing to significant scientific value and extensive application prospects, such as electrohydrodynamic atomization, 1,2 electrospinning, 3 electrophoresis, 4 electrowetting, 5 and droplet manipulation in microfluidic devices 6,7 . Particularly in petroleum and petrochemical industries, the high‐voltage electric field is widely used in the process of electric dehydration and electric desalting 8–10 .…”
Section: Introductionmentioning
confidence: 99%